Removal of Reactive Red 141 Dye from Aqueous Solution by Titanium Hydroxyapatite Pellets. Issue 1 (2nd January 2016) - Asjadi, Fatemeh; Salahi, Esmaeil; Mobasherpour, Iman
Abstract : The adsorption of Reactive Red 141 over the pressed and calcined pellets of TiHAp and HAp was investigated by using continuous reflux system. Langmuir isotherm model was found to be the best model to describe the equilibrium data, with maximum adsorption capacity of 20.62 and 28.41 (mg g −1 ) for HAp and TiHAp, respectively. Kinetics data was best described by the pseudo-second-order model and intraparticle diffusion determined as sole controlling step of adsorption process. Possible mechanisms of the adsorption dye on the HAp and TiHAp were discussed. GRAPHICAL ABSTRACT: